Perinatal outcomes in women of the program of assisted reproductive technologies in conditions of anthropogenic load - Kokorina, Nadezhda V.; Kalenkovich, Тatiana Yu.; Grac, Liudmila V.; Alferovich, Elena N. (Journal of the Belarusian State University. Ecology, 2019)
The article presents an analysis of perinatal outcomes in induced pregnancies in couples with various forms of infertility. It is established that children conceived with the help of assisted reproductive technologies (ART) are a high-risk group and have a busy period of early adaptation due to posthypoxic complications. The favorable outcome of ART is largely dependent on the state of health of the pregnant woman being pregnant and the primary causes of infertility, as well as the number of implanted embryos.